2021
DOI: 10.3389/fmed.2021.644515
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Management of Pandemic Risks in Dental Practice: A Consolidated Framework for COVID-19 Control in Dentistry

Abstract: Dental teams and their workplaces are among the most exposed to airborne and bloodborne infectious agents, and therefore at the forefront of pandemic-related changes to how dental care is organized and provided to patients. The increasing complexity of guidelines makes is challenging for clinicians to navigate the multitude of COVID-19 guidelines issued by different agencies. A comparative analysis of guidance issued for managing COVID-19 in dental settings leading U.S. agencies was conducted, including docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
1
14
0
3
Order By: Relevance
“…Relatedly, our study results revealed how changing and often contradictory COVID-19 federal guidelines, also identified by other scholars, 26 often burdened oral health care providers, as did divergent recommendations from state public health agencies and trusted professional associations, including the American Dental Association, American Association of Public Health Dentistry, and American Public Health Association. Our study results also elucidated the limitations of dental preparedness frameworks that assume adequate and dependable material resources (for example, Benzian 26 ) or do not account for these resources (for example, Brondani and Donnelly 25 ). By contrast, our participants described using substandard PPE, reusing limited PPE beyond its recommended life, or delaying patients' needed care owing to unobtainable supplies.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Relatedly, our study results revealed how changing and often contradictory COVID-19 federal guidelines, also identified by other scholars, 26 often burdened oral health care providers, as did divergent recommendations from state public health agencies and trusted professional associations, including the American Dental Association, American Association of Public Health Dentistry, and American Public Health Association. Our study results also elucidated the limitations of dental preparedness frameworks that assume adequate and dependable material resources (for example, Benzian 26 ) or do not account for these resources (for example, Brondani and Donnelly 25 ). By contrast, our participants described using substandard PPE, reusing limited PPE beyond its recommended life, or delaying patients' needed care owing to unobtainable supplies.…”
Section: Discussionsupporting
confidence: 66%
“…Participants' concerns about infection control among patients, staff members, and personal contacts were unsurprising, given the characteristics of the SARS-CoV-2 pathogen, the centrality of infection control in dentistry, and emerging dental PHEPR. 12,25,26,41,42 Although participants felt confident about controlling blood-borne pathogens, their excess stress related to the novel risks of a highly infectious air-and droplet-borne pathogen in the dental space was exacerbated by 2 systemslevel and 1 patient-level concerns; that is, differences in guidance from governmental and professional bodies, the unpredictability of material resource pipelines (in particular PPE), and the urgency participants felt to return patients to in-person care to manage, halt, or prevent disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, for periodontal treatments, manual scaling was chosen over ultrasonic scaling. In cases of symptomatic irreversible pulpitis, biological methods, such as pulpotomy or pulpectomy, were recommended as much as possible [ 14 ]. On the other hand, in patients with extensive destruction of the hard dental tissue accompanied by severe pain, it was necessary to opt for the extraction of the affected tooth.…”
Section: Pre- During and Post-pandemic Particular Aspects Of Dental T...mentioning
confidence: 99%
“…The risk for transmission of pathogens in a dental office resulting in an infectious disease is still unknown; it seems to be limited in developed countries but it cannot be considered negligible [106]. The literature review revealed five distinct areas of pandemic control, comprising (1) planning and protocols, (2) patient screening, (3) preparation of facilities, (4) PPE and infection control, and (5) practices and aerosol control; thereby covering systematically all aspects needing adaptation in a pandemic context [107].…”
Section: Introductionmentioning
confidence: 99%